Preparation method and application of troxerutin
Through two stages of reaction, the purity and yield of troclutin was successfully improved by using specific catalysts and reaction conditions, solving the problems of complex and cost-effective preparation of troclutin in the prior art, and achieving efficient and economical preparation of troclutin.
Patent Information
- Application Number
- CN202411721003.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
In the prior art, the preparation method of tricepin is cumbersome and expensive, and is not suitable for industrial promotion, so it is difficult to effectively control the reaction process to increase the proportion of trihydroxyethyl rutin.
Through two stages of reaction, sodium hydroxide and sodium methoxide are used as catalysts, combined with ethylene oxide, and the main product is generated under specific conditions. Then, in the second stage, sodium carboxymethylcellulose and sodium alginate are used as catalysts, combined with 2-chloroethanol or ethylene oxide, the content of trihydroxyethylrutin is further increased.
The preparation of high-purity trakrutin has been achieved, with a purity of more than 99%, a yield of more than 93%, and a simple process and low cost, which is suitable for industrial production.
Smart Images

Figure CN119529006A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical pharmacy, and in particular to a preparation method and application of high-purity troxerutin. Background Art
[0002] Troxerutin is also known as Vinaroluton, trihydroxyethyl rutin, etc. Its chemical name is 7,3',4'-hydroxyethyl rutin (referred to as trihydroxyethyl rutin), and its molecular formula is C 33 H 42 O 19 , the chemical structure is as follows:
[0003]
[0004] Troxerutin is a type of anticoagulant and thrombolytic drug that inhibits the aggregation of red blood cells and platelets, prevents thrombosis, and increases the oxygen content in the blood, improves microcirculation, and promotes the formation of new blood vessels to enhance collateral circulation. It has a protective effect on endothelial cells, can counteract vascular damage caused by serotonin and bradykinin, increase the resistance of capillaries, reduce the permeability of capillaries, and prevent edema caused by increased vascular permeability. It also has anti-radiation damage, anti-inflammatory, anti-allergic, and anti-ulcer effects.
[0005] At present, the preparation method of troxerutin is basically based on rutin and ethylene oxide as raw materials, with methanol, ethanol and / or water as solvent, and Willanson etherification nucleophilic substitution reaction occurs in the presence of alkaline catalyst. Because rutin has a polyhydroxy structure, the reaction product is a mixture of monohydroxyethyl rutin, dihydroxyethyl rutin, trihydroxyethyl rutin and tetrahydroxyethyl rutin, but the strongest physiological activity in the mixture of troxerutin is trihydroxyethyl rutin (i.e. 7,3', 4'-hydroxyethyl rutin). In the prior art, the focus of research and development is: how to control the reaction process, select the input raw materials and proportioning, so that the ratio of trihydroxyethyl rutin in the product is the highest. In existing reports, the method of troxerutin content reaching more than 98.0% includes chromatography, purifying rutin in advance, reducing the ratio of tetrahydroxyethyl rutin by complexing mode, refining with adsorbent, etc., which is cumbersome to operate and too costly, and is not suitable for industrialization and promotion. Summary of the invention
[0006] The invention prepares high-purity troxerutin by two-stage reaction. In each stage, a specific catalyst and a reaction substrate are selected to achieve the preparation of high-purity troxerutin under specific reaction conditions. After simple purification, the purity can reach more than 99%, and the yield can reach more than 93%.
[0007] A method for preparing troxerutin comprises the following steps:
[0008] (1) Pour the reaction solvent methanol into a reaction kettle, add rutin, sodium hydroxide, and sodium methoxide in sequence, stir evenly, add ethylene oxide, then introduce inert gas, adjust the pressure of the reaction kettle to 0.4-0.6Mpa, heat to 75-85°C, stir and react for 4-8h, and then keep warm; wherein the weight ratio of rutin to methanol is 1:4-6, the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:(0.5-0.6), and the weight ratio of rutin to ethylene oxide is 1:(0.14-0.18);
[0009] (2) When the pH value of the reaction liquid in the reactor is 9-10, an acidic solvent is added to the reaction liquid to neutralize the reaction liquid to a pH value of 7.5-8, the temperature is lowered to 45-55° C., and then sodium carboxymethyl cellulose and sodium alginate are added. After stirring evenly, 2-chloroethanol or ethylene oxide is added, and the stirring reaction is continued for 4-8 hours and then the temperature is kept warm; wherein the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:(0.5-0.6);
[0010] (3) adding an acidic solvent to the reaction solution to neutralize the reaction solution to a pH value of 5-6, and standing the solution for crystallization to obtain trihydroxyethyl rutin;
[0011] (4) Mix and dissolve trihydroxyethylrutin and a purification solvent in a ratio of 1 g: 25-30 mL, heat to 50-60° C., reflux for 1-1.5 h, cool, grow crystals at room temperature for 10-15 h, and then centrifuge and filter, and dry to obtain the purified troxerutin.
[0012] In step (1), the weight ratio of rutin to methanol is 1:5, the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.55, and the weight ratio of rutin to ethylene oxide is 1:0.16.
[0013] In step (2), the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.55, the weight ratio of rutin to 2-chloroethanol is 1:(0.2-0.26), and the weight ratio of rutin to ethylene oxide is (0.11-0.14).
[0014] The purification solvent described in step (4) is one or more of methanol, ethanol or isopropanol, the feed ratio of trihydroxyethylrutin to the purification solvent is 1g:28mL, the dissolution temperature is 55°C, the reflux time is 1.2h, and the crystal growth time is 12h.
[0015] The inert gas is nitrogen, and the acidic solvent is hydrochloric acid or glacial acetic acid.
[0016] The invention realizes the preparation of high-purity troxerutin through two-stage reaction, and each stage realizes the preparation of high-purity troxerutin under specific reaction conditions by selecting specific catalysts and reaction bottom materials. In the first stage, by selecting specific catalysts of sodium hydroxide and sodium methoxide, and coordinating with ethylene oxide, a product mainly containing monohydroxyethyl rutin, dihydroxyethyl rutin and a small amount of troxerutin (trihydroxyethylated rutin) is generated under certain conditions. In the second stage, by adjusting the pH value, replacing sodium carboxymethyl cellulose and sodium alginate as catalysts in a specific ratio, and coordinating with 2-chloroethanol or ethylene oxide, the reaction needs to be continued at a low temperature of 45-55° C., thereby realizing the preparation of high-purity troxerutin. After purification, the purity can reach more than 99%, and the yield reaches more than 93%.
[0017] In the first stage of the present invention, sodium hydroxide and sodium methoxide are used as catalysts. Sodium methoxide is an organic base, and sodium hydroxide is an inorganic base. The mixture of the two has strong alkalinity. If the ratio is not appropriate, decomposition, precipitation and other unstable phenomena may occur after mixing. Too high a temperature may cause the mixed solution to decompose, and too low a temperature may affect the reaction activity of the mixed solution. Therefore, the ratio of the two and the reaction temperature are particularly important. The present invention greatly enhances the catalytic effect by selecting a specific ratio while ensuring stability and activity.
[0018] The second stage of the present invention adjusts the pH value and re-adds the natural catalyst sodium carboxymethyl cellulose and sodium alginate, both of which have weak alkalinity, and cooperates with the reaction substrate, especially 2-chloroethanol, to greatly enhance the targeted selection of the reaction, and through the selection and coordination of conditions such as temperature and time, the content of trihydroxyethyl rutin is improved, and it is particularly noted that the reaction temperature should be in the range of 45-55°C, not too high or too low, and the adjusted pH value should be coordinated to act together, otherwise the reaction activity will be affected. In addition, the order of addition of the catalyst is also very important. The change in the order of addition of the two-stage catalyst will affect the purity and yield of the product, that is, the order of addition of the catalyst has a significant impact on the purity and yield of troxerutin, and it also indirectly proves that the second stage can only achieve the technical effect by using sodium carboxymethyl cellulose and sodium alginate composite catalyst in combination with a specific pH value and reaction temperature.
[0019] The invention comprises the following steps: mixing and dissolving trihydroxyethyl rutin and a purification solvent, heating and refluxing, growing crystals at room temperature for 10-15 hours, and then centrifugally filtering and drying to obtain purified troxerutin.
[0020] The invention realizes a breakthrough in a new method by selecting raw materials, controlling the ratio and reaction conditions through a two-stage reaction, and achieves a technical effect of a purity of more than 99% and a yield of more than 93% only through the selection and control of basic elements. Therefore, the invention is different from the prior art methods of purifying rutin in advance, purifying by chromatography, reducing the proportion of tetrahydroxyethyl rutin by complexation, refining by adsorbent, etc. The invention has the advantages of low cost, simple steps, economy, environmental protection, suitability for industrial production, and the like.
[0021] Furthermore, the present invention also relates to an orally disintegrating tablet containing troxerutin:
[0022] An orally disintegrating tablet of troxerutin, wherein the orally disintegrating tablet contains a disintegrant, a filler, a binder, and a lubricant. Preferably, the orally disintegrating tablet of the present invention further contains a flavoring agent;
[0023] Preferably, the disintegrant in the present invention is selected from cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate; more preferably, the mass ratio of the two is 1:0.5;
[0024] The fillers in the present invention are anhydrous calcium hydrogen phosphate and mannitol, wherein the role of calcium hydrogen phosphate is to increase the particle density of the disintegrating tablet; more preferably, the mass ratio of the two is 1:2;
[0025] The binder in the present invention is ethyl cellulose. The inventor surprisingly found that the binder ethyl cellulose in the present invention is a water-insoluble binder. When it is used in combination with the cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate defined in the present invention, its specific structure and performance can cooperate with the disintegrant, so that the disintegrant can more effectively exert a greater disintegration force, accelerate disintegration, and achieve an excellent disintegration effect.
[0026] The lubricant in the present invention is silicified microcrystalline cellulose;
[0027] Furthermore, the content of troxerutin, disintegrant, filler, binder and lubricant in the present invention is in the following ratio by mass:
[0028] Troxerutin: 30-40%
[0029] Disintegrant: 11-20%
[0030] Fillers: 40-50%
[0031] Binder: 1-3%
[0032] Lubricant: 0.1-1%
[0033] Flavoring agent: 0.2-0.8%
[0034] The disintegrating tablet of the present invention can be prepared by freeze drying, spray drying or wet granulation conventional in the art;
[0035] In the present invention, the ratio of the disintegrating tablet is optimized. Preferably, when troxerutin is 35%, the disintegrant is cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio is 1:0.5) 14%, the filler is anhydrous calcium hydrogen phosphate and mannitol (mass ratio is 1:2) 48%, the binder is ethyl cellulose: 2%, the lubricant is silicified microcrystalline cellulose: 0.5%, and the flavoring agent is 0.5%, the disintegration time of the disintegrating tablet is 18s.
[0036] Furthermore, the present invention also relates to a multi-layer sustained-release dressing containing troxerutin:
[0037] The present invention also provides a multi-layered drug sustained-release dressing, which is specifically configured as follows:
[0038] A multilayer dressing with a controllable troxerutin drug release function, the multilayer dressing contains a multilayer structure: a multilayer structure with different drug concentration gradients, and utilizes the gradient change of drug concentration between different layers to achieve controlled drug release.
[0039] Preferably, the multilayer dressing of the present invention is a three-layer structure, wherein the dosage of troxerutin in the bottom layer is 8-10wt%, in the middle layer is 2-4wt%, and in the upper layer is 0.3-0.8wt%. The drug release rate is regulated by changing the drug concentration of different layers; during the drug release process, since the drug concentration in the upper layer is low, the release process is relatively slow, and as the multilayer structure of drug release deepens, the drug concentration gradually increases, but the difficulty of release increases. The present invention controls the drug release rate by controlling the multilayer structure and drug concentration. Furthermore, the present invention can also adjust the thickness of each layer in the multilayer to adjust the drug release rate;
[0040] Preferably, the fibers of each layer in the multilayer structure of the present invention are prepared from nanofibers having a core-shell structure;
[0041] Preferably, the nanofibers with a core-shell structure in the bottom layer of the present invention are composed as follows:
[0042] Core layer: PVP and troxerutin, wherein the amount of troxerutin is consistent with the content in the bottom layer.
[0043] Shell: Polylactic acid (PLA)
[0044] In the core-shell structure, troxerutin is soluble in water, but through the encapsulation of PLA, it can slow down the dissolution in water, thereby achieving the effect of drug sustained release. The core-shell structure can further achieve the effect of drug sustained release compared with a single co-spinning structure.
[0045] Preferably, the polylactic acid used in the present invention is poly(L-lactic acid) (PLLA); its molecular weight is 30000-50000;
[0046] Preferably, in the core-shell structure of the bottom layer, the molecular weight of the polylactic acid can be adjusted to adjust the sustained release time of the drug in the bottom layer. Preferably, the molecular weight of the polylactic acid is 80,000-200,000, and more preferably, the molecular weight of the polylactic acid is 140,000.
[0047] The preparation method of the core-shell nanofibers is as follows:
[0048] According to the required drug loading amount, PVP, troxerutin and solvent are mixed to prepare a core layer solution; polylactic acid and solvent are selected as the mixed shell layer solution; preferably, the solvent is a conventional electrospinning solvent in the art; preferably chloroform, dichloromethane, DMF, ethanol, acetone, etc.;
[0049] A coaxial electrospinning device is selected, and the solutions of the shell layer and the core layer are respectively introduced into the coaxial spinning head of the spinning device, and the spinning parameters are set to prepare nanofibers with a core-shell structure. Furthermore, for the core-shell structure, the sustained release performance of the drug can be adjusted by setting the length of the core layer fiber and the length of the shell layer fiber in combination.
[0050] Preferably, the voltage of the coaxial electrospinning device for the core layer is 20Kv, the spinning speed is 0.6mL / h, and the spinning distance is 20cm; the spinning voltage for the shell solution is 20Kv, the spinning speed is 1.2mL / h, and the spinning distance is 20cm; the middle layer and the upper layer also adopt a similar preparation process to the bottom layer;
[0051] Preferably, in the present invention, the spinning speeds of the shell layer and the core layer can be set to obtain sustained-release dressings with different core-shell structures and sustained-release effects.
[0052] The composition of the nanofiber with middle core-shell structure is as follows:
[0053] Core layer: graphene oxide-polyethylene glycol, troxerutin,
[0054] Shell: Chitosan, poly(lactic-co-glycolic acid) (PLGA)
[0055] Preferably, the molecular weight of polyethylene glycol is 30000-50000, wherein the molecular weight of polylactic acid-glycolic acid is 100000-110000; the mass ratio of graphene oxide to polyethylene glycol is 2-5:5-8; the mass ratio of chitosan to PLGA is: 2-5:5:8;
[0056] The present invention introduces a polylactic acid-glycolic acid copolymer into the shell layer in the middle layer. The copolymer has hydrophobic properties, and troxerutin itself is soluble in water. The hydrophobic properties are enhanced in the middle layer, which can effectively slow down the release of the drug and avoid the problem of sudden drug release caused by the increase of internal drug concentration.
[0057] Nanofibers with core-shell structure:
[0058] Nuclear layer: polydopamine, carboxymethylcellulose, troxerutin.
[0059] Shell: Polyglycolic acid (PGA)
[0060] In the upper layer, due to the low concentration of the drug, polydopamine is selected, which has an adhesion effect on the drug and can better disperse the drug; preferably, the mass ratio of polydopamine to carboxymethyl cellulose is: 0.8-1:4-5
[0061] For the shell layer, polyglycolic acid is selected, wherein the molecular weight thereof is 30,000-50,000, preferably, the molecular weight thereof is 40,000;
[0062] Preferably, the diameter of the core-shell nanofibers of the present invention is 500-800 nm;
[0063] The present invention adopts nanofibers with a core-shell structure, which can wrap fibers containing drugs inside, so as to wrap the drugs well and maintain the activity of the drugs. At the same time, due to the effect of its shell, it can effectively regulate the slow release of the internal drugs, avoid sudden release, and reduce the side effects of the drugs.
[0064] In the present invention, the nanofibers with core-shell structure are prepared into multilayer films, which have high specific surface area and high porosity, so that the overall drug loading is controllable and more uniform. The multilayer dressing structure can extend the drug diffusion distance, the drug effect can be more lasting, and the sustained-release performance is good. It can be used as a dressing in a variety of different environments to improve the application range of the drug.
[0065] In the present invention, by adopting a core-shell structure in the material of the layer and setting a drug concentration gradient from the inside to the outside for a specific core-shell structure and a multi-layer dressing, the uniformity of the troxerutin drug loading is improved, while the problem of sudden drug release is avoided, thereby improving the application range of the drug. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 Schematic diagram of the preparation of multilayer dressing DETAILED DESCRIPTION
[0067] The effects and results of the method of the present invention are further described below with reference to the embodiments, but are not limited to the following embodiments.
[0068] Example 1
[0069] A method for preparing troxerutin comprises the following steps:
[0070] (1) Pour the reaction solvent methanol into a reactor, add rutin, sodium hydroxide, and sodium methoxide in sequence, stir evenly, add ethylene oxide, then introduce inert gas, adjust the pressure of the reactor to 0.5 MPa, heat to 80° C., stir and react for 6 hours, and then keep warm; wherein the weight ratio of rutin to methanol is 1:5, the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.55, and the weight ratio of rutin to ethylene oxide is 1:0.16;
[0071] (2) When the pH value of the reaction liquid in the reactor is 9.5, hydrochloric acid solvent is added to the reaction liquid to neutralize the pH value of the reaction liquid to 7.8, and the temperature is lowered to 50° C., and then sodium carboxymethyl cellulose and sodium alginate are added. After stirring evenly, 2-chloroethanol is added, and the stirring reaction is continued for 6 hours and then the temperature is kept warm; wherein the weight ratio of rutin to 2-chloroethanol is 1:0.23, and the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.55;
[0072] (3) adding an acidic solvent to the reaction solution to neutralize the reaction solution to a pH value of 5.5, and standing the solution for crystallization to obtain trihydroxyethyl rutin;
[0073] (4) trihydroxyethylrutin and ethanol were mixed and dissolved in a feed ratio of 1 g:28 mL, and the temperature was raised to 55° C., refluxed for 1.2 h, cooled, and crystallized at room temperature for 12 h, and then centrifuged and filtered, and dried to obtain the obtained product, namely purified troxerutin.
[0074] Example 1-1
[0075] The difference between this embodiment and embodiment 1 is that the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.5.
[0076] Example 1-2
[0077] The difference between this embodiment and embodiment 1 is that the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.6.
[0078] Comparative Example 1-1
[0079] The difference between this comparative example and Example 1 is that the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.4.
[0080] Comparative Example 1-2
[0081] The difference between this comparative example and Example 1 is that the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.7.
[0082] Example 2-1
[0083] The difference between this embodiment and embodiment 1 is that the heating temperature in step (1) is 75°C.
[0084] Example 2-2
[0085] The difference between this embodiment and embodiment 1 is that the heating temperature in step (1) is 85°C.
[0086] Comparative Example 2-1
[0087] The difference between this comparative example and Example 1 is that the heating temperature in step (1) is 70°C.
[0088] Comparative Example 2-2
[0089] The difference between this comparative example and Example 1 is that the heating temperature in step (1) is 90°C.
[0090] Example 3-1
[0091] The difference between this embodiment and embodiment 1 is that in step (2), hydrochloric acid solvent is added to the reaction solution to neutralize the reaction solution to a pH value of 7.5.
[0092] Example 3-2
[0093] The difference between this embodiment and embodiment 1 is that in step (2), hydrochloric acid solvent is added to the reaction solution to neutralize the reaction solution to a pH value of 8.
[0094] Comparative Example 3-1
[0095] The difference between this comparative example and Example 1 is that in step (2), hydrochloric acid solvent is added to the reaction solution to neutralize the reaction solution to a pH value of 7.0.
[0096] Comparative Example 3-2
[0097] The difference between this comparative example and Example 1 is that in step (2), hydrochloric acid solvent is added to the reaction solution to neutralize the reaction solution to a pH value of 8.5.
[0098] Example 4-1
[0099] The difference between this embodiment and embodiment 1 is that the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.5.
[0100] Example 4-2
[0101] The difference between this embodiment and embodiment 1 is that the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.6.
[0102] Comparative Example 4-1
[0103] The difference between this comparative example and Example 1 is that the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.4.
[0104] Comparative Example 4-2
[0105] The difference between this comparative example and Example 1 is that the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.7.
[0106] Example 5-1
[0107] The difference between this embodiment and embodiment 1 is that the temperature in step (2) is lowered to 45° C. for reaction.
[0108] Example 5-2
[0109] The difference between this embodiment and embodiment 1 is that the temperature in step (2) is lowered to 55° C. for reaction.
[0110] Comparative Example 5-1
[0111] The difference between this comparative example and Example 1 is that the temperature in step (2) is lowered to 40°C for reaction.
[0112] Comparative Example 5-2
[0113] The difference between this comparative example and Example 1 is that the temperature in step (2) is lowered to 60°C for reaction.
[0114] Example 6-1
[0115] The difference between this embodiment and embodiment 1 is that in step (1), the weight ratio of rutin to ethylene oxide is 1:0.14.
[0116] Example 6-2
[0117] The difference between this embodiment and embodiment 1 is that in step (1), the weight ratio of rutin to ethylene oxide is 1:0.18.
[0118] Comparative Example 6-1
[0119] The difference between this comparative example and Example 1 is that the weight ratio of rutin to ethylene oxide in step (1) is 1:0.12.
[0120] Comparative Example 6-2
[0121] The difference between this comparative example and Example 1 is that the weight ratio of rutin to ethylene oxide in step (1) is 1:0.2.
[0122] Example 7-1
[0123] The difference between this embodiment and embodiment 1 is that in step (2), the weight ratio of rutin to 2-chloroethanol is 1:0.2.
[0124] Example 7-2
[0125] The difference between this embodiment and embodiment 1 is that in step (2), the weight ratio of rutin to 2-chloroethanol is 1:0.26.
[0126] Comparative Example 7-1
[0127] The difference between this comparative example and Example 1 is that the weight ratio of rutin to 2-chloroethanol in step (2) is 1:0.18.
[0128] Comparative Example 7-2
[0129] The difference between this comparative example and Example 1 is that the weight ratio of rutin to 2-chloroethanol in step (2) is 1:0.28.
[0130] Example 8-1
[0131] The difference between this embodiment and embodiment 1 is that the 2-chloroethanol in step (2) is replaced by ethylene oxide, and the weight ratio of rutin to ethylene oxide is 1:0.11.
[0132] Example 8-2
[0133] The difference between this embodiment and embodiment 1 is that the 2-chloroethanol in step (2) is replaced by ethylene oxide, and the weight ratio of rutin to ethylene oxide is 1:0.14.
[0134] Comparative Example 8-1
[0135] The difference between this comparative example and Example 1 is that the 2-chloroethanol in step (2) is replaced by ethylene oxide, and the weight ratio of rutin to ethylene oxide is 1:0.08.
[0136] Comparative Example 8-2
[0137] The difference between this comparative example and Example 1 is that the 2-chloroethanol in step (2) is replaced by ethylene oxide, and the weight ratio of rutin to ethylene oxide is 1:0.16.
[0138] Comparative Example a
[0139] The difference between this comparative example and Example 1 is that the sodium hydroxide and sodium methoxide in step (1) are replaced by sodium hydroxide alone, and the weight ratio of rutin to sodium hydroxide is 100:0.95.
[0140] Comparative Example b
[0141] The difference between this comparative example and Example 1 is that the sodium hydroxide and sodium methoxide in step (1) are replaced by only sodium methoxide, and the weight ratio of rutin to sodium methoxide is 100:0.95.
[0142] Comparative Example c
[0143] The difference between this comparative example and Example 1 is that the sodium carboxymethyl cellulose and sodium alginate in step (2) are replaced by sodium carboxymethyl cellulose alone, and the weight ratio of rutin to sodium carboxymethyl cellulose is 100:1.05.
[0144] Comparative Example d
[0145] The difference between this comparative example and Example 1 is that the sodium carboxymethyl cellulose and sodium alginate in step (2) are replaced by sodium alginate alone, and the weight ratio of rutin to sodium alginate is 100:1.05.
[0146] Comparative Example e
[0147] The difference between this comparative example and Example 1 is that the types of catalysts in step (1) and step (2) are interchanged, that is, rutin, sodium carboxymethyl cellulose, and sodium alginate are added in a weight ratio of 100:0.5:0.55 in step (1), and rutin, sodium hydroxide, and sodium methoxide are added in a weight ratio of 100:0.4:0.55 in step (2).
[0148] The purity and yield of the troxerutin prepared in each embodiment and comparative example were tested, and the test results are shown in Table 1.
[0149] Table 1 Troxerutin purity and yield test results
[0150]
[0151]
[0152] As can be seen from the above, in the first stage of the present invention, sodium hydroxide and sodium methoxide are used as catalysts together, and the catalytic effect can be improved by combining the selection of parameters such as ratio and temperature; in the second stage, the pH value is adjusted, and the natural catalysts sodium carboxymethyl cellulose and sodium alginate are added again. The alkalinity of the two is relatively weak, and the reaction substrate, especially 2-chloroethanol, can greatly enhance the targeted selection of the reaction, and the content of trihydroxyethylrutin is improved by the selection and coordination of conditions such as temperature and time. It can be seen from the series of Examples 3 and 5 that the influence of pH value and reaction temperature on the purity and yield of troxerutin is very critical; the order of addition of the catalyst is also very important. Comparative Example e adjusts the order of addition of the two-stage catalyst, and the purity and yield are sharply reduced, proving that the order of addition of the catalyst has a significant effect on the purity and yield of troxerutin. The invention does not add an adsorbent, and purifies by means of crystal growing, filtering and drying. It is not necessary to purify rutin in advance, and it is not necessary to reduce the proportion of tetrahydroxyethyl rutin by means of complexation. Only by selecting the type of catalyst in the first stage, adjusting the pH value in the second stage, adding sodium carboxymethyl cellulose and sodium alginate in a specific proportion with weaker alkalinity as catalysts for continued reaction, and controlling the reaction temperature, the purity and yield are improved. At the same time, the invention has the advantages of low cost, simple steps, economy, environmental protection, suitability for industrial production, and the like.
[0153] Example 9-1: An orally disintegrating tablet containing troxerutin. The troxerutin in the following examples and comparative examples is prepared from Example 1;
[0154] The disintegrating tablet of the present invention is prepared according to the following weight ratio:
[0155] Troxerutin 35%, disintegrants cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio of 1:0.5) 14%, fillers anhydrous calcium hydrogen phosphate and mannitol (mass ratio of 1:2): 48%, binder ethyl cellulose: 2%, lubricant silicified microcrystalline cellulose: 0.5%, flavoring agent: 0.5%.
[0156] Example 9-2:
[0157] Troxerutin 35%, disintegrants cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio of 1:0.5) 14%, fillers anhydrous calcium hydrogen phosphate and mannitol (mass ratio of 1:2): 48%, binder ethyl cellulose: 3%, lubricant silicified microcrystalline cellulose: 0.5%, flavoring agent: 0.5%.
[0158] Example 9-3:
[0159] Troxerutin 36%, disintegrants cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio of 1:0.5) 18%, fillers anhydrous calcium hydrogen phosphate and mannitol (mass ratio of 1:2) 50%, binder ethyl cellulose 3%, lubricant silicified microcrystalline cellulose 0.5%, flavoring agent 0.5%.
[0160] Comparative Example 9-1:
[0161] Troxerutin 35%, disintegrants cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio of 1:0.5) 10%, fillers anhydrous calcium hydrogen phosphate and mannitol (mass ratio of 1:2) 52%, binder ethyl cellulose 2%, lubricant silicified microcrystalline cellulose 0.5%, flavoring agent 0.5%.
[0162] Comparative Example 9-2:
[0163] Troxerutin 35%, disintegrants cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate (mass ratio of 1:0.5) 21%, fillers anhydrous calcium hydrogen phosphate and mannitol (mass ratio of 1:2) 38%, binder ethyl cellulose 5%, lubricant silicified microcrystalline cellulose 0.5%, flavoring agent 0.5%.
[0164] Comparative Example 9-3: The difference in composition from Example 1 is that only one disintegrant is used, cross-linked polyvinylpyrrolidone, and the dosage is kept at 14%;
[0165] Comparative Example 9-4: The difference in composition from Example 1 is that only one disintegrant is used, sodium alginate, and the dosage is kept at 14%;
[0166] Comparative Example 9-5: The difference between the composition of Example 1 and that of Example 1 is that the binder is water-soluble hydroxypropyl cellulose, and the amount is kept at 2%.
[0167] Comparative Example 9-6: The difference in composition from Example 1 is that the lubricant used is magnesium lauryl sulfate, and the dosage is 0.5%.
[0168] Example: According to the disintegration time limit detection method under General Rules 0921 of Part IV of the 2020 edition of the Chinese Pharmacopoeia, the disintegration time of the above-mentioned Examples 9-1, 9-2 and 9-3 and Comparative Examples 1-4 were tested.
[0169] The results are shown in Table 2:
[0170] Table 2 Disintegration time of each embodiment and comparative example
[0171] Example Disintegration time (S) Example 9-1 18 Example 9-2 20 Example 9-3 19 Comparative Example 9-1 40 Comparative Example 9-2 35 Comparative Example 9-3 28 Comparative Example 9-4 32 Comparative Example 9-5 26 Comparative Example 9-6 31
[0172] It can be seen from the above results that in the present invention, by optimizing the selection and ratio of various excipients in the disintegrant, the disintegration time of the orally disintegrating tablet is as short as 18s. It can be seen from Comparative Examples 1-4 that only within the numerical range specified by the present invention can the disintegration time be optimal; further, two disintegrant combinations are used in this application, and when only one is used, the disintegration time is longer; only when the two are used in combination can the optimal disintegration time be achieved. The reason is that the disintegration mechanism of cross-linked polyvinylpyrrolidone is deformation recovery, and sodium alginate is swelling disintegration. On this basis, by selecting water-insoluble ethyl cellulose as a binder, silicified microcrystalline cellulose with a certain disintegrating force as a lubricant, and cross-linked polyvinylpyrrolidone and sodium alginate with different disintegration mechanisms, and optimizing the ratio, an orally disintegrating tablet with excellent disintegration performance is obtained.
[0173] The present invention further relates to a multi-layer sustained-release dressing containing troxerutin. The troxerutin used in the following examples and comparative examples is the troxerutin prepared in Example 1.
[0174] Example 10-1: A multi-layer sustained-release dressing containing troxerutin:
[0175] Preparation of lower fiber membrane:
[0176] Core layer: PVP and troxerutin, add 1g of PVP and a certain amount of troxerutin into 10mL of chloroform solution, stir until completely dissolved, and prepare the core layer solution;
[0177] Shell layer: polylactic acid (PLA), 1 g of L-polylactic acid (PLLA) with a molecular weight of 140,000 was dispersed in 10 mL of dichloromethane solution to prepare a shell layer solution.
[0178] The solutions of the shell layer and the core layer configured as above are respectively guided to the coaxial spinning head of the spinning equipment, and the spinning parameters are set to prepare nanofibers with a core-shell structure. The voltage of the coaxial electrospinning equipment for the core layer is 20Kv, the spinning speed is 0.6mL / h, and the spinning distance is 20cn; the spinning voltage for the shell layer solution is 20Kv, the spinning speed is 1.2mL / h, and the spinning distance is 20cm. The spun fibers with a core-shell structure are prepared at room temperature, and the prepared fibers are vacuum dried to prepare a lower membrane;
[0179] Preparation of middle fiber membrane:
[0180] Core layer: 0.5 g of graphene oxide, 1 g of polyethylene glycol and the required amount of troxerutin were dissolved in 15 mL of ethanol solution and stirred until dissolved to prepare a core layer spinning solution.
[0181] Shell layer: 0.8 g chitosan and 1 g poly(lactic acid-co-glycolic acid) (PLGA) (molecular weight 100,000) were dissolved in 20 mL of DMF solution and stirred until dissolved to prepare a shell spinning solution;
[0182] It is prepared by the same spinning process as the lower membrane;
[0183] Preparation of upper fiber membrane:
[0184] Core layer: 0.3 g of polydopamine, 1.2 g of carboxymethyl cellulose and a certain amount of troxerutin were dissolved in 18 mL of dichloromethane and stirred until dissolved to prepare a core layer spinning solution.
[0185] Shell layer: 1 g of polyglycolic acid (PGA) (molecular weight 40,000) was dissolved in 13 mL of DMF solution to prepare a shell spinning solution;
[0186] It is prepared by the same spinning process as the lower membrane;
[0187] In the preparation process of the multi-layer dressing, electrospinning is used to prepare a three-layer nanofiber membrane by layered continuous deposition.
[0188] In the prepared three-layer nanofiber membrane, the dosage of troxerutin in the lower layer is 10wt%, in the middle layer is 4wt%, and in the upper layer is 0.8wt%.
[0189] Example 10-2:
[0190] The same as Example 10-1, wherein the dosage of troxerutin in the three is changed, the dosage of troxerutin in the lower layer is 8wt% of the high molecular weight, the dosage in the middle layer is 2wt%, and the dosage in the upper layer is 0.3wt%.
[0191] Example 10-3:
[0192] The same as Example 10-1, wherein the dosage of troxerutin in the three is changed, the dosage of troxerutin in the lower layer is 9wt% of the high molecular weight, the dosage in the middle layer is 3wt%, and the dosage in the upper layer is 0.5wt%.
[0193] Comparative Example 10-1:
[0194] The difference from Example 10-1 is that the drug concentration of troxerutin in the three layers is the same, which is 4 wt %;
[0195] Comparative Example 10-2:
[0196] The difference from Example 10-1 is that the drug concentration of troxerutin in the three layers is the same, which is 10wt%;
[0197] Comparative Example 10-3:
[0198] The difference from Example 10-1 is that the drug concentration of troxerutin in the three layers is the same, which is 0.8wt%;
[0199] Comparative Example 10-4:
[0200] The same as Example 10-1, except that the multilayer structure is prepared by using fibers prepared by co-spinning the shell layer and the core layer in the three layers;
[0201] Example:
[0202] The in vitro sustained release capacity of the drugs of Examples 10-1 to 10-3 and Comparative Examples 10-1 to 10-4 was determined by UV-visible spectrophotometry using a PBS solution at a temperature of 37°C;
[0203] The specific results are shown in Table 3:
[0204] Table 3 Drug sustained release effects of Examples and Comparative Examples
[0205]
[0206] Therefore, it can be seen from the above data that the present invention achieves excellent drug sustained-release performance through the setting of specific core-shell structure fibers and the setting of multilayer nanofilms with specific concentration gradients; and through comparative examples, it can be seen that when co-spinning of materials or a single concentration is adopted, the sustained-release performance is weaker than that of the embodiments of the present invention; in the present invention, through the specific multilayer concentration gradient setting and the specific raw material selection in the core-shell structure in the single layer, the multilayer structure finally prepared has excellent drug sustained-release effect and can be applied to a variety of scenarios.
[0207] The present invention is not limited to the above-mentioned embodiments. For those skilled in the art, any improvements made without departing from the principle of the present invention are also considered to be within the protection scope of the present invention.
Claims
1. A method for preparing troxerutin, characterized in that: The steps include: (1) Pour the reaction solvent methanol into a reaction kettle, add rutin, sodium hydroxide, and sodium methoxide in sequence, stir evenly, add ethylene oxide, then introduce inert gas, adjust the pressure of the reaction kettle to 0.4-0.6Ma, heat to 75-85°C, stir and react for 4-8h, and then keep warm; wherein the weight ratio of rutin to methanol is 1:4-6, the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:(0.5-0.6), and the weight ratio of rutin to ethylene oxide is 1:(0.14-0.18); (2) When the pH value of the reaction liquid in the reactor is 9-10, an acidic solvent is added to the reaction liquid to neutralize the reaction liquid to a pH value of 7.5-8, the temperature is lowered to 45-55° C., and then sodium carboxymethyl cellulose and sodium alginate are added. After stirring evenly, 2-chloroethanol or ethylene oxide is added, and the stirring reaction is continued for 4-8 hours and then the temperature is kept warm; wherein the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:(0.5-0.6); (3) adding an acidic solvent to the reaction solution to neutralize the reaction solution to a pH value of 5-6, and standing the solution for crystallization to obtain trihydroxyethyl rutin; (4) Mix and dissolve trihydroxyethylrutin and a purification solvent in a ratio of 1 g: 25-30 mL, heat to 50-60° C., reflux for 1-1.5 h, cool, grow crystals at room temperature for 10-15 h, and then centrifuge and filter, and dry to obtain the purified troxerutin.
2. The method for preparing troxerutin according to claim 1, wherein: In step (1), the weight ratio of rutin to methanol is 1:5, the weight ratio of rutin to sodium hydroxide and sodium methoxide is 100:0.4:0.55, and the weight ratio of rutin to ethylene oxide is 1:0.
16.
3. The preparation method of troxerutin according to claim 1 or 2, characterized in that: In step (2), the weight ratio of rutin to sodium carboxymethyl cellulose and sodium alginate is 100:0.5:0.55, the weight ratio of rutin to 2-chloroethanol is 1:(0.2-0.26), and the weight ratio of rutin to ethylene oxide is (0.11-0.14).
4. The method for preparing troxerutin according to any one of claims 1 to 3, characterized in that: The purification solvent described in step (4) is one or more of methanol, ethanol or isopropanol, the feed ratio of trihydroxyethylrutin to the purification solvent is 1g:28mL, the dissolution temperature is 55°C, the reflux time is 1.2h, and the crystal growth time is 12h.
5. The method for preparing troxerutin according to any one of claims 1 to 4, characterized in that: The inert gas is nitrogen, and the acidic solvent is hydrochloric acid or glacial acetic acid.
6. A troxerutin sustained-release dressing with a multi-layer structure, characterized in that: The multilayer structure has a three-layer structure, wherein the three-layer structure consists of a bottom layer, a middle layer and a surface layer, and the drug content of troxerutin gradually decreases from the bottom layer to the surface layer; the troxerutin in the sustained-release dressing is prepared by any preparation method of claims 1-5.
7. The multi-layered troxerutin sustained-release dressing according to claim 6, characterized in that: The drug content of troxerutin in the bottom layer is 8-10wt%, in the middle layer is 2-4wt%, and in the upper layer is 0.3-0.8wt%. The drug release speed can be regulated by setting the drug concentration changes in different layers.
8. An orally disintegrating tablet containing troxerutin, characterized in that: The orally disintegrating tablet contains a disintegrant, a filler, a binder, and a lubricant. The orally disintegrating tablet of the present invention also contains a flavoring agent; preferably, the disintegrant in the present invention is cross-linked polyvinylpyrrolidone (PPVP) and sodium alginate; more preferably, the mass ratio of the two is 1:0.5; the filler in the present invention is anhydrous calcium hydrogen phosphate and mannitol; preferably, the mass ratio of the two is 1:2; the binder is ethyl cellulose, and the lubricant is silicified microcrystalline cellulose; wherein troxerutin is prepared by any one of the preparation methods of claims 1-5.
9. The orally disintegrating tablet according to claim 8, characterized in that: The proportion of each component in mass percentage is: Troxerutin: 30-40%; Disintegrant: 11-20%; Fillers: 40-50%; Binder: 1-3%; Lubricant: 0.1-1%; Flavoring agent: 0.2-0.8%.